Rancang Bangun Prototipe Keamanan Ruang Laboratorium dengan Pintu Otomatis Menggunakan Sensor Suhu MLX90614 Berbasis Arduino Atmega 2560 - Diana Margarini; Sri Wahyu Suciyati; Arif Surtono; Gurum Ahmad Pauzi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Research on laboratory room security system has begun to be developed with various kinds of inputs used. In this study, the design of a laboratory room security prototype with automatic doors has been realized using the MLX90614 temperature sensor based on Arduino Atmega 2560. The design of this prototype aims to design a prototype laboratoey room with automatic doors using a door lock solenoid and a temperature sensor MLX90614. In addition, this system is equipped with a counter to reduce and add people in the room using the FC-51 infrared sensor. Data retrieval is done by detecting human temperature before entering the room, when the temperature input is met, the door of the room will open with a maximum limit of 10 people. The results showed that the system was functioning properly, indicated by the state of the door that could open when it received an input of temperature between 35-37°C, the door remained closed when detecting of temperature other than 35-37°, and the door remained closed when the object in the room was up to 10 people.